先化简再求值x^2+x-6/x^4-13x^2+36 (其中x=-3)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 12:25:20
先化简再求值x^2+x-6/x^4-13x^2+36(其中x=-3)先化简再求值x^2+x-6/x^4-13x^2+36(其中x=-3)先化简再求值x^2+x-6/x^4-13x^2+36(其中x=-
先化简再求值x^2+x-6/x^4-13x^2+36 (其中x=-3)
先化简再求值x^2+x-6/x^4-13x^2+36 (其中x=-3)
先化简再求值x^2+x-6/x^4-13x^2+36 (其中x=-3)
原式=(x-2)(x+3)/[(x²-4)(x²-9)]
=(x-2)(x+3)/[(x+2)(x-2)(x+3)(x-3)]
=1/[(x+2)(x-3)]
=1/[(-3+2)(-3-3)]
=1/6
先化简再求值x^2+x-6/x^4-13x^2+36 (其中x=-3)
先化简再求值 x-1分之4(x-x)+(x-2)
先化简再求值 x^2-6x+9/x^2-4 其中x=3
先化简再求值(x+3x+5x+7x+.+101x)-(2x+4x+6x+...100x),其中x=51分之2
先化简再求值先化简再求值:(x-x/x+1)(x+1/x^2+4x+4)(x^2-4/x^2-2x),其中x=-0.5
先化简再求值x/x²-1(x-1/x-2)
先化简再求值:(x+2-12/x-2)/(4-x)/(x-2),其中x=-1/2
先化简再求值:-(X^2+3x)+2(4x+x^2),其中X=-2
先化简再求值 3x^3-[-x^2-2(x-x^6)] x=-1
(x+2)的平方+(2x+1))(2x-1)-4x(x+1)先化简再求值
先化简再求值:(x-4)(x-2)-(x-1)(x-3)其中x=-5/2
(x-3)(x+4)-2(x+5)(x-5),其中x-10先化简再求值
先化简再求值:3x^3-[x^3+(6x^2-7x)]-2(x^3-3x^2-4x),其中x=-1
先化简再求值:3x^3-[x^3+(6x^2-7x)]-2(x^3-3x^2-4x),其中x=-1
先化简再求值3x³-[x³+(6x²-7x)]-2(x³-3x²-4x),其中x=-1
2x^2-4x-6=0求值
先化简再求值[3x/(x+2)-x/(x-2)]÷2x/(x^2-4)x=2010
先化简再求值(x/x-2-x/x+2)÷4x/x-2,其中x=1